Validation of the Italian Version of the Brief Emotional Intelligence Scale (BEIS-10). Issue 5 (October 2021) - Durosini, Ilaria; Triberti, Stefano; Ongaro, Giulia; Pravettoni, Gabriella
Based on Salovey and Mayer's conceptualization of emotional intelligence, Davies and colleagues developed the BEIS-10 scale, a 10-items self-report questionnaire that explores individual dispositions that people have about exploring one's own and others' emotions. To date, no studies assess the validity of the BEIS-10 scale in the Italian context. This article aims to fill this gap, exploring the validity, reliability, and construct validity of the Italian version of this scale. 244 Italian adults participated in the study and 67 respondents completed a second administration of the scale after two-weeks. The recommended statistical procedures were followed to validate the Italian version of the BEIS-10 scale and, after a back-translation process and a pilot testing, the five-factor structure of the scale was tested through a confirmatory factor analysis. Results highlighted that the five-factor model of emotional intelligence proposed by Davies and colleagues (2010) is confirmed in the Italian population. Data showed good reliability, good stability over time, and evidence of construct validity of the BEIS-10 scale. The BEIS-10 scale could be completed in a couple of minutes and it is particularly useful for collecting data in contexts in which time is an issue.